2022
DOI: 10.1097/scs.0000000000009046
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Operation of Severe Orbital Hypertelorism With Computer-Assisted Precise Virtual Plan

Abstract: Orbital hypertelorism correction is still a less precise procedure, with a simple preoperative design and surgical results often depending on the operator’s experience. In recent years, computer-assisted technology has been fully utilized in craniofacial surgery. This article aims to explore the clinical results of computer-assisted technology in orbital hypertelorism correction and discuss its advantages and effects on treatment. Four patients with orbital hypertelorism underwent intracranial and extracranial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Ouyang et al reported a successful case of orbital hypertelorism correction with the aid of a 3D-printed cutting guide. The study created a 1:1 plaster model of the skull with a predetermined osteotomy guideline that assisted in surgical planning and served as an intraoperative guide [ 58 ]. Another team conducted forty cases of computer-assisted craniofacial malformity surgeries, treating hypertelorism, craniosynostosis, and orbital trauma with the aid of 3D-printed cutting guides.…”
Section: 3d Printing In Ophthalmic Prototyping and Simulationmentioning
confidence: 99%
“…Ouyang et al reported a successful case of orbital hypertelorism correction with the aid of a 3D-printed cutting guide. The study created a 1:1 plaster model of the skull with a predetermined osteotomy guideline that assisted in surgical planning and served as an intraoperative guide [ 58 ]. Another team conducted forty cases of computer-assisted craniofacial malformity surgeries, treating hypertelorism, craniosynostosis, and orbital trauma with the aid of 3D-printed cutting guides.…”
Section: 3d Printing In Ophthalmic Prototyping and Simulationmentioning
confidence: 99%